The Effect of Reading, Questioning and Answering Strategy toward Student Creative Thinking on Evolution Course at Biology Department FMIPA Universitas Negeri Padang - Rahmawati Darussyamsu; Muhyiatul Fadilah (Bioeducation Journal, 2017)
Biology Department Universitas Negeri Padang students’ creative thinking competence in evolution was low. This fact assumed can be solved using RQA strategy and Molecular Evolution learning book that have developed. This research conducted to know the effect of using RQA strategy and learning book to students’ concept understanding compared with the other class that used conventional method. The samples were 46 students. Data was posttest score in evolution used creative thinking instrument that have been validated by expert and analyzed used t-test. The result showed value 0,313>0,05; it concluded that there were no significant different of students’ creative thinking competence between students at experiment class and control.